Journal on Data Semantics VIII - Spaccapietra, Stefano; Atzeni, Paolo; Fages, Francois; Hacid, Mohand-Said.; Kifer, Michael; Mylopoulos, John.; Pernici, Barbara; Shvaiko, Pavel; Zaihrayeu, Ilya.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
• Semantic caching • Data warehousing and semantic data mining • Spatial, temporal, multimedia and multimodal semantics • Semantics in data visualization • Semantic services for mobile users • Supporting tools • Applications of semantic-driven approaches These topics are to be understood as specifically related to semantic issues. Contributions submitted to the journal and dealing with semantics of data will be considered even if they are not from the topics in the list. While the physical appearance of the journal issues is like the books from the we- known Springer LNCS series, the mode of operation is that of a journal. Contributions can be freely submitted by authors and are reviewed by the Editorial Board. Contributions may also be invited, and nevertheless carefully reviewed, as in the case for issues that contain extended versions of best papers from major conferences addressing data semantics issues. Special issues, focusing on a specific topic, are coordinated by guest editors once the proposal for a special issue is accepted by the Editorial Board. Finally, it is also possible that a journal issue be devoted to a single text.
23rd International Conference on Conceptual Modeling (ER 2004) -- Default Clustering with Conceptual Structures -- Workshop on Context and Ontologies: Theory,Practice and Applications (C&O 2005) -- Context Dependency Management in Ontology Engineering: A Formal Approach -- Encoding Classifications into Lightweight Ontologies -- Second International Conference on Ontologies,DataBases and Applications of SEmantics (ODBASE 2005) -- GeRoMe: A Generic Role Based Metamodel for Model Management -- Metadata Management in a Multiversion Data Warehouse -- International Workshop on Principles and Practice of Semantic Web Reasoning (PPSWR 2005) -- SomeRDFS in the Semantic Web -- A Tool for Evaluating Ontology Alignment Strategies -- 7th International Conference on Data Warehousing and Knowledge Discovery (DAWAK 2005) -- Processing Sequential Patterns in Relational Databases.
Keywords: Data structures (Computer science).; Database management; Information storage and retrieval; Artificial intelligence; Application software; Computer communication systems; Data Structures and Information Theory; Database Management; Information Storage and Retrieval; Artificial Intelligence; Information Systems Applications (incl. Internet).; Computer Communication Networks